KONSTRUKSI KEBIJAKAN BERBASIS BUKTI BAGI PENINGKATAN KUALITAS MADU HUTAN DI INDONESIA - Levina A.G Pieter; Marcellinus M.B Utomo (Jurnal Agroforestri Indonesia, 2020)
Attention to the development of Sumbawan honey is still lacking, despite the economic potential of Sumbawa honey can actually be felt even in remote villages. Currently, regional policies focusing on developing forest honey business and improving its quality have not been initiated. Therefore, this research is aimed at mapping technical, social, and governance issues in an effort to increase the economic benefits of honey; and testing the water content of Sumbawa forest honey and compare it with the standards listed in the Indonesian National Standard (SNI). As an end result, this study recommends the necessary local policies to address the issues raised. Through field exploration and semi-structured interviews with 30 respondents, technical, social and governance issues for Sumbawa honey can be mapped. Through testing 15 samples of forest honey harvested from 3 districts on the island of Sumbawa, there were only 7 samples that had water content less than 22% or met SNI standards. Therefore, the water content of the Sumbawa forest honey needs to be lowered to meet SNI honey standards and to increase market share. We conclude that local governments need to proactively go to the field with their policy tools to improve the quality and quantity of marketable honey. This study recommends a policy package that allows the District Office of Industry and Trade or the District Office of Cooperatives and MSMEs to play an active role in the knot of reducing water content and the knot of buying and selling forest honey.